Estudo dos defeitos no fluorofosfato de sódio e vanádio, Na3V2(PO4)2F3, através da modelagem computacional - Silva, Carlos Henrique Prado (2022)
Sodium vanadium fluorophosphate Na3V2(PO4)2F3 has been attracting a lot of attention as a promising cathode for sodium ion batteries due to its high performance and stable 3D open structure. In this work, the static computational modeling method was used for the structural study of intrinsic and extrinsic defects in Na3V2(PO4)2F3. The procedure initially carried out was to model the parameters of the potentials that reproduced the structural and physical properties of Na3V2(PO4)2F3. Then, the solution energy for the intrinsic defects was calculated and it was observed that the Na Frenkel, Na2O anti-Schottky and NaF Schottky defects had the lowest solution energy. The next step was to study the defects arising from the insertion of trivalent rare earth ions in the Na3V2(PO4)2F3 lattice. All calculations were performed using the GULP computational package. It was found that the most likely defect is the one in which the trivalent rare earth dopants replace the V 3+ sites, in which case the mechanisms with the lowest solution energy were isovalent. The results indicate that the trivalent rare earth dopant (R 3+ = Yb e Er) at the site of V 3+ are the most energetically favorable dopants for Na3V2(PO4)2F3.